Bark tissue transcriptome analyses of inverted Populus yunnanensis cuttings reveal the crucial role of plant hormones in response to inversion - An-Pei Zhou; Pei-Hua Gan; Dan Zong; Xuan Fei; Yuan-Yuan Zhong; Si-Qi Li; Jin-De Yu; Cheng-Zhong He (PeerJ, 2019)
Inverted cuttings of Populus yunnanensis exhibit an interesting growth response to inversion. This response is characterized by enlargement of the stem above the shoot site, while the upright stem shows obvious outward growth below the shoot site. In this study, we examined transcriptome changes in bark tissue at four positions on upright and inverted cuttings of P. yunnanensis: position B, the upper portion of the stem; position C, the lower portion of the stem; position D, the bottom of new growth; and position E, the top of new growth. The results revealed major transcriptomic changes in the stem, especially at position B, but little alteration was observed in the bark tissue of the new shoot. The differentially expressed genes (DEGs) were mainly assigned to four pathways: plant hormone signal transduction, plant-pathogen interaction, mitogen-activated protein kinase (MAPK) signaling pathway-plant, and adenosine triphosphate-binding cassette (ABC) transporters. Most of these DEGs were involved in at least two pathways. The levels of many hormones, such as auxin (IAA), cytokinin (CTK), gibberellins (GAs), ethylene (ET), and brassinosteroids (BRs), underwent large changes in the inverted cuttings. A coexpression network showed that the top 20 hub unigenes at position B in the upright and inverted cutting groups were associated mainly with the BR and ET signaling pathways, respectively. Furthermore, brassinosteroid insensitive 1-associated receptor kinase 1 (BAK1) in the BR pathway and both ethylene response (ETR) and constitutive triple response 1 (CTR1) in the ET pathway were important hubs that interfaced with multiple pathways.